Investigation of microbial diversity in geothermal hot springs in Unkeshwar, India, based on 16S rRNA amplicon metagenome sequencing - Mehetre, Gajanan T.; Paranjpe, Aditi; Dastager, Syed Gulam; Dharne, Mahesh S. (Genome Announcements, 2016)
Microbial diversity in geothermal waters of the Unkeshwar hot springs in Maharashtra, India, was studied using 16S rRNA amplicon metagenomic sequencing. Taxonomic analysis revealed the presence of Bacteroidetes , Proteobacteria , Cyanobacteria , Actinobacteria , Archeae , and OD1 phyla. Metabolic function prediction analysis indicated a battery of biological information systems indicating rich and novel microbial diversity, with potential biotechnological applications in this niche.